MANAGEMENT OF THORACOLUMBAR SPINE INJURIES AT A TERTIARY CARE HOSPITAL - Raja, Riaz A. (Journal of Ayub Medical College Abbottabad, 2010)
Background: The purpose of descriptive case series study was to see the conservative and surgical outcome in respect of neurological improvement, sphincter functions and early ambulation in cases of traumatic thoracolumbar injuries in a tertiary care hospital. Methods: This was a hospital based prospective study comprised of 50 thoracolumbar injury cases registered during the period of 1 year from September 2005 to September 2006. All cases were evaluated for their clinical features. During initial phase, level and degree of neurological injury was assessed using Frankle grades. Operative and postoperative record with x-rays and MRI were maintained. The follow-up ranged from 6 to 12 months with clinical and radiological assessment. Results: A total of 50 cases were registered, 43 (86%) were males and 7 (14%) were females. Fall was the most common cause of injury (92%). The most common level involved was L1 (46%). The 2nd common site of injury was T12 (12%). The treatment given was conservative in 42.55%, and surgery was performed on 57.44%. Three (6.38%) patients were left against medical advice. Conclusion: Thoracolumbar injuries occur in young population and creates socio-economic burden to the society. Patients with partial neurological deficit benefit from surgery. Keywords: Spinal injury, Thoracolumbar, Fall, Road Traffic Accident